EVALUATION OF THE TRANSPARENCY OF LEGAL ONLINE LENDING PLATFORMS IN TERMS OF COSTS: A LITERATURE REVIEW OF INTEREST RATES, TERMS, AND PENALTIES - Gunawan Widjaja (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The development of legal online lending services in Indonesia has opened up quick and easy access to financing for the public, but on the other hand, it has raised challenges related to the transparency of loan cost information. This study aims to evaluate the transparency of the main cost components on legal online lending platforms, which include interest rates, loan terms, and late fees through a literature review and analysis of current regulations. The results of the study show that although the regulations of the Financial Services Authority (OJK) and the guidelines of the Indonesian Joint Funding Fintech Association (AFPI) set limits and disclosure obligations, implementation in the field is still varied and not yet fully transparent to consumers. The lack of information transparency has the potential to pose financial risks to borrowers and affect public trust in legal online lending services. This study recommends strengthening regulations, supervision, and consumer education as strategic steps to improve transparency and consumer protection in the fintech lending ecosystem in Indonesia.